Incorporation and in vitro release of doxorubicin in thermally sensitive micelles made from poly(N-isopropylacrylamide-co-N,N-dimethylacrylamide)-b- poly(D,L-lactide-co-glycolide) with varying compositions - Liu, S.Q. (2014)
10.1016/j.biomaterials.2005.01.030